Analysing the challenges in stakeholder relationship management in the healthcare process: a social network perspective. (23rd March 2022) - Ali, Farooq; Haapasalo, Harri; Tampio, Kari-Pekka; Haapasalo, Henriikka
We investigate stakeholder relationship management and identify challenges that impact relationships at the healthcare process level using the inductive research approach. We adopt an inductive approach and grounded theory method since there is a need for detailed descriptions on stakeholder network, especially on relationship management. The emergent grounded theoretical model explains the challenges that impact stakeholder relationship management, i.e., gaps in the healthcare network, challenges in articulating a healthcare vision, triggers of challenges, contextual challenges, healthcare landscape, challenges in trust-building, and collaboration. Additionally, our findings show how the network structure and stakeholders' position in the network, based on their interactions' patterns, influence stakeholder relationship management. The grounded theory that emerged from our study confirms several themes and their interrelationships, which constitute our main contribution.